2020
DOI: 10.1186/s40729-020-00255-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peri-implant soft tissue and crestal bone status of dental implants placed in prediabetic, type 2 diabetic, and non-diabetic individuals: a retrospective cohort study

Abstract: Background Clinicoradiographic status of narrow-diameter implants (NDIs) among patients with prediabetes and type 2 diabetes mellitus (DM) is scarce. The aim was to address the clinicoradiographic status of NDIs placed prediabetic, type 2 diabetic, and non-diabetic individuals. In this retrospective cohort study, patients having undergone oral rehabilitation with NDI were included. The participants were divided into the following: (a) patients with prediabetes; (b) patients with poorly controlled type 2 DM; (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
(42 reference statements)
0
10
0
1
Order By: Relevance
“…It is well established that an immunosuppressed systemic health (for instance un-controlled DM) is a risk factor for oral diseases including periodontitis and peri-implantitis. 29,[33][34][35] Similarly, habitual use of electronic nicotine delivery systems and combustible tobacco (such as cigarettes and waterpipe/narghile/shisha) is also directly linked with the prognosis and occurrence of periodontal and peri-implant diseases. [36][37][38][39][40][41] Therefore, strict inclusion criteria were used in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that an immunosuppressed systemic health (for instance un-controlled DM) is a risk factor for oral diseases including periodontitis and peri-implantitis. 29,[33][34][35] Similarly, habitual use of electronic nicotine delivery systems and combustible tobacco (such as cigarettes and waterpipe/narghile/shisha) is also directly linked with the prognosis and occurrence of periodontal and peri-implant diseases. [36][37][38][39][40][41] Therefore, strict inclusion criteria were used in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One reasoning for similarity in PISF volumes and CL in patients who received MD with or without photobiomodulation is that strict inclusion measures were imposed in the present study. It is well established that an immunosuppressed systemic health (for instance un‐controlled DM) is a risk factor for oral diseases including periodontitis and peri‐implantitis 29,33–35 . Similarly, habitual use of electronic nicotine delivery systems and combustible tobacco (such as cigarettes and waterpipe/narghile/shisha) is also directly linked with the prognosis and occurrence of periodontal and peri‐implant diseases 36–41 …”
Section: Discussionmentioning
confidence: 99%
“…Alshahrani ve ark. 18 ise yaptıkları çalışmada implant çevresi hastalık (peri-implant mukozitis ve peri-implantitis) gelişme riskinin zayıf kontrol altındaki diyabetik bireylerde iyi glisemik kontrol altındaki bireyler ve sistemik sağlıklı bireyler ile karşılaştırıldığında daha yüksek olduğunu bildirmiştir. Bunun yanısıra, son zamanlardaki bazı sistematik derlemeler ve meta analizler kronik hipergliseminin implant çevresi hastalıklarda önemli bir risk faktörü olduğunu bildirirken 19,20 , ancak son bulgular diyabet ve implant çevresi hastalıklar arasında önemli bir ilişki olmadığını bildirmektedir.…”
Section: Discussionunclassified
“…Therefore, the proposed hypothesis was rejected. This hypothesis was based on previous work and clinical trials which reported a significant decline in periodontal parameters, periimplantitis, and loss of alveolar bone with paresthesia around dental implants among diabetics when compared to non-diabetics [ 22 , 28 , 29 , 30 ]. The outcomes of in-vivo studies reported that among participants with T2DM the intensity of parameters assessed is predisposed by glycemic status.…”
Section: Discussionmentioning
confidence: 99%